2017
DOI: 10.1007/s11665-017-2531-z
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-Mo-Zr-Cr Biomedical Alloys by Powder Metallurgy

Abstract: Elshalakany, AB.; Ali, S.; A. Amigó Mata; Eessaa, AK.; Mohan, P.; Osman, T.; Amigó, V. (2017). Microstructure and Mechanical Properties of Ti-Mo-Zr-Cr Biomedical Alloys by Powder Metallurgy. ABSTRACTTitanium and its alloys have been widely used as biometals due to their excellent biocompatibility, corrosion resistance and moderate mechanical properties. Ti-15Mo-6Zr based alloys and a series of Ti-15Mo-6Zr-xCr (x = 1, 2, 3, 4 wt. %) alloys were designed and fabricated by powder metallurgy for the first time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…5.4% less than Ti-12Mo-6Zr. Elashalakany et al (Elshalakany et al, 2017) also claimed that volumetric shrinkage for their alloy (Ti-15Mo-6Zr-xCr) is between 16-20% which is like our alloy. Delvat et al (Delvat et al, 2008) also claimed that dimensional loss of Ti-20Mo and Ti-40Mo are between (20-23)%.…”
Section: Chapter 5: Discussion Of the Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…5.4% less than Ti-12Mo-6Zr. Elashalakany et al (Elshalakany et al, 2017) also claimed that volumetric shrinkage for their alloy (Ti-15Mo-6Zr-xCr) is between 16-20% which is like our alloy. Delvat et al (Delvat et al, 2008) also claimed that dimensional loss of Ti-20Mo and Ti-40Mo are between (20-23)%.…”
Section: Chapter 5: Discussion Of the Resultssupporting
confidence: 64%
“…Ti-6Al-7Nb with powder metallurgy has grain size is in range of (134 ± 17) μm at sintering temperature 1250ºC which is claimed by Bolzoni et al (Bolzoni et al, 2013) and this value is much more than our alloy. (Elshalakany et al, 2017). Fracture characteristics of these alloys are like our alloys which is prepared by powder metallurgy technique.…”
Section: Chapter 5: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Ti alloys, the most common for dental and orthopedic applications are materials formed by Ti, aluminum (Al) and vanadium (V) like Ti-6Al-4 V and other β-phasetype alloys as the ones with high contents of β-stabilizers (V, Cr, molybdenum (Mo), Fe, niobium (Nb), and tantalum (Ta)) [5][6][7][8][9][10][11][12]. However, several reports point to the V in the Ti-6Al-4 V as toxic [13,14], being a motivation for exploring further V-free options.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that the porous surfaces assist on the fixations and ingrowth of organic tissue, improve the body fluid, reduce the mechanical mismatch due to lower elastic modulus values, and reduce the failure rate of implants [3]. Examples of the above are Ti and indium (In) as (Ti-In) [18], Ti-Mo [7][8][9], Ti, Nb and Tin (Sn) as Ti-Nb-Sn [10,19], Ti and zirconium (Zr) as Ti-Zr [20], and Ti and silver (Ag) as Ti-Ag [21] alloys. However, some of the previous systems employ alloying elements that are still not widely studied, being a reason why several in vivo tests of biocompatibility should be carried out to determine their biological feasibility.…”
Section: Introductionmentioning
confidence: 99%